DEVELOPING THE LEXIC COMPETENCE OF HIS STUDENTS IN THE CONTEXT OF LINGUISTIC TERMS - Shadiyeva, Shahnoza (Журнал иностранных языков и лингвистики, 2023)
Our article addresses the issue of forming the lexical competence of university students in a foreign language and presents basic concepts related to the lexical side of foreign language teaching. It focuses on lexical skills related to linguistic concepts as part of the lexical competence of a foreign language, taking into account the linguistic features of the language material and the pedagogical and cognitive activity of students.